Dadaism (Re)activated. Artzins and Dada - Lachman, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The article analyses in what way artzins (independent art and literary journals published in Poland in the 1980s and 1990s) drew inspiration from the Dada tradition, and how they made its philosophy live again. Artzins are seen here both as a medium of literature and art and as specific forms of artistic expression (press art). The article attempts to show why artzins and their authors were interested in reviving the avant-garde and Dada ideas. It also investigates how Dadaism functions today in the form of contemporary works and styles which are influenced by this avant-garde movement. What is more, the article tries to answer the question about the nature and definition of Dadaism shaped and reflected by today's artistic projects.